Pengaruh Etika Kerja Dan Lingkungan Kerja Terhadap Komitmen Organisasi Melalui Kepuasan Kerja Pada Kantor Walikota Medan - Nurhalizah, Mutia; Jufrizen, Jufrizen (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
The purpose of this study was to determine and analyze the effect of work ethics on organizational commitment, the influence of the work environment on organizational commitment, the influence of work ethics on job satisfaction, the influence of the work environment on job satisfaction, the effect of job satisfaction on organizational commitment, the influence of work ethics on organizational commitment through job satisfaction, and the influence of the work environment on organizational commitment through job satisfaction. This research uses associative research with a sample of 76 respondents who are employees of the Kantor Walikota Medan. Data collection techniques using interviews and a list of statements such as questionnaires and data analysis techniques using Partial Least Square (SmartPls) to test the seven hypotheses proposed in this study. The results of the study show that work ethic has no effect on organizational commitment, work environment has no effect on organizational commitment, work ethic has a significant effect on job satisfaction, work environment has a significant effect on job satisfaction, job satisfaction has a significant effect on organizational commitment, work ethic has a significant effect on commitment. organization through job satisfaction (in other words job satisfaction acts as a mediator), the work environment has a significant effect on organizational commitment through job satisfaction (in other words job satisfaction acts as a mediator).